Activation of transient receptor potential vanilloid 4 protects articular cartilage against inflammatory responses via CaMKK/AMPK/NF-κB signaling pathway - Hattori, Kyosuke (Sci Rep, 2021)
Transient receptor potential vanilloid 4 (TRPV4) plays an important role in chondrocytes via Ca(2+) signaling. However, its role in the progression of osteoarthritis is unclear. This study aimed to evaluate the effects of TRPV4 activation on articular cartilage and chondrocytes stimulated with interleukin (IL)-1β. Bovine and human articular chondrocytes were stimulated with various agents, including IL-1β, GSK1016790A (GSK101; a TRPV4 agonist), Compound C (an AMP-activated protein kinase (AMPK) inhibitor), and STO-609 (a calmodulin-dependent protein kinase kinase (CaMKK) inhibitor), and were processed for Western blot analysis and real-time PCR. The dimethylmethylene blue (DMMB) assay and Safranin O staining were also performed. GSK101 reversed the IL-1β-induced increase in expression of matrix metalloproteinase (MMP)-13 and decrease in expression of aggrecan. GSK101 also decreased proteoglycan release in the DMMB assay and retained Safranin O staining of articular cartilage tissue. Furthermore, GSK101 increased AMPK phosphorylation and decreased IL-1β-induced nuclear factor kappa B (NF-κB) phosphorylation. Compound C and STO-609 reversed the suppressive effects of GSK101 on NF-κB activation and MMP-13 expression. In conclusion, TRPV4 activation had chondroprotective effects on articular cartilage stimulated with IL-1β by activating CaMKK/AMPK and suppressing the NF-κB pathway. TRPV4 activators may offer a promising therapeutic option for preventing the progression of osteoarthritis.